Spectrum of cosmic rays with energy above $10^{17}$ eV - Knurenko, S P; Egorova, V P; Glushkov, A V; Ivanov, A A; Krasilnikov, A D; Makarov, I T; Mikhailov, A A; Olzoyev, V V; Pravdin, M I; Sabourov, A V; Sleptsov, I Ye; Struchkov, G G (2004)
There are some discrepancies in the results on energy spectrum from Yakutsk, AGASA, and HiRes experiments. In this work differential energy spectrum of primary cosmic rays based on the Yakutsk EAS Array data is presented. For the largest events values of $S_{600}$ and axes coordinates have been obtained using revised lateral distribution function. Simulation of converter's response at large distances showed no considerable underestimation of particle density. Complex shape of spectrum in region of $\E > 10^{17}$ eV is confirmed. After adjustment of parameters and additional exposition at the Yakutsk array there are three events with energy $\E > 10^{20}$ eV.